Identification of an OmpW homologue in Burkholderia pseudomallei, a protective vaccine antigen against melioidosis. Issue 23 (17th May 2016) - Casey, William T.; Spink, Natasha; Cia, Felipe; Collins, Cassandra; Romano, Maria; Berisio, Rita; Bancroft, Gregory J.; McClean, Siobhán
Highlights: BpOmpW protein with SAS adjuvant protected Balb/C mice against lethal infection with 75% survival. Potent serological responses were observed. BpOmpW resulted in prolonged protection of C57BL/6 mice for up to 80 days. Abstract: Burkholderia pseudomallei is the causative agent of melioidosis, which is associated with a range of clinical manifestations, including sepsis and fatal pneumonia and is endemic in Southeast Asia and Northern Australia. Treatment can be challenging and control of infection involves prolonged antibiotic therapy, yet there are no approved vaccines available to prevent infection. Our aim was to develop and assess the potential of a prophylactic vaccine candidate targeted against melioidosis. The identified candidate is the 22 kDa outer membrane protein, OmpW. We previously demonstrated that this protein was immunoprotective in mouse models of Burkholderia cepacia complex (Bcc) infections. We cloned Bp_ompW in Escherichia coli, expressed and purified the protein. Endotoxin free protein administered with SAS adjuvant protected Balb/C mice (75% survival) relative to controls (25% survival) ( p  < 0.05). A potent serological response was observed with IgG2a to IgG1 ratio of 6.0. Furthermore C57BL/6 mice were protected for up to 80 days against a lethal dose of B. pseudomallei and surpassed the efficacy of the live attenuated 2D2 positive control. BpompW is homologous across thirteen sequenced B. pseudomallei strains, indicating that it should be broadly protective against B. pseudomallei . In conclusion, we have demonstrated that BpOmpW is able to induce protective immunity against melioidosis and is likely to be an effective vaccine antigen, possibly in combination with other subunit antigens.